New acid BisGMA analogs for dental adhesive applications with antimicrobial activity. Issue 12 (December 2016) - Melinte, Violeta; Buruiana, Tinca; Chibac, Andreea; Mares, Mihai; Aldea, Horia; Buruiana, Emil C.
Graphical abstract: Highlights: Acid-modified BisGMA derivatives were synthesized and characterized. Photopolymerization of experimental adhesives was evaluated by FTIR spectroscopy. Resin samples with Ag nanoparticles, Zn methacrylate and triclosan were tested against Streptococcus mutans and Candida albicans . The inhibition of microorganism growth at the contact of composite films with bacteria was evidenced. Abstract: Objective: To achieve bisphenol A glycerolate dimethacrylate (BisGMA) analogs with reduced viscosity to be used in the formulation of dental adhesives containing biocidal components. Methods: A series of low-viscosity BisGMA derivatives ( η : 39–12 Pa s) modified with 30, 60 and, respectively 80 mol% carboxylic acid units were synthesized and characterized. Hydrogen bonding interactions in our monomers, the photopolymerization behavior and implicitly the conversion degree (DC) for some experimental adhesive formulations containing acid-modified BisGMA, commercial BisGMA (only in F1–F3), triethyleneglycol dimethacrylate and 2-hydroxyethyl methacrylate were examined by FTIR spectroscopy. The water effects on the photocrosslinked networks together with the flexural strength/modulus were also investigated. The adhesive penetration into the dentin surface was surveyed by SEM analysis, and the antimicrobial activity triggered by the incorporation of 0.5 wt% AgNO3, 10 wt% zinc methacrylate or 1 wt% triclosan methacrylate in selected adhesive formulations on the growth of Streptococcus mutans and Candida albicans strains was evidenced. Results: The contribution of the hydrogen bonding interactions was found to be lower in BisGMA derivatives than in non-modified BisGMA, and the DC varied between 56.5 (F6) and 83.7% (F1) compared with a control formulation based on BisGMA:TEGDMA (DC = 58.2%). The flexural strength and flexural modulus varied in the range 33.7 MPa (F6)–54.4 MPa (F8) MPa and 0.64 (F6)–1.43 (F8) GPa, respectively. SEM observation of adhesive-dentin interface revealed the formation of resin tags for the carboxyl-containing adhesive, while for the control adhesive they are hardly formed. Also, the microorganism development was inhibited, the proposed materials displaying antimicrobial activity. Significance: The experimental formulations based on carboxyl-functionalized BisGMA exhibit a similar or even improved behavior over control sample, suggesting their potential applicability as antimicrobial dental adhesives.